2020
DOI: 10.1021/acscatal.9b04925
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Pt–N3 Sites on the Stable Covalent Triazine Framework Nanosheets for Photocatalytic N2 Fixation

Abstract: The commercial Haber-Bosch process for NH3 production not only requires large amounts of energy and hydrogen supply but also generates tremendous greenhouse CO2 emission. To mitigate energy and environmental challenges, renewable ammonia production technologies based on electrochemical and photochemical methods, in particular, photocatalytic nitrogen fixation in aqueous phase for ammonia production is highly desired. In the present work, single-atom Pt anchored at the −N3 sites of stable and ultrathin covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
180
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(194 citation statements)
references
References 66 publications
13
180
1
Order By: Relevance
“…[ 11 ] The production of green H 2 is of great importance to lower the energy consumption and environmental damage by the current industrial processes like steam‐reforming of methane. [ 12 ] As the storage of H 2 is trickier, ammonia (NH 3 ) has been recognized as a potential option for H 2 storage due to its high hydrogen content and is the backbone of fertilizer industries. Currently, NH 3 is prepared by the Bosch–Haber process, which is not very economical and consumes a huge amount of energy due to its harsh reaction requirements.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] The production of green H 2 is of great importance to lower the energy consumption and environmental damage by the current industrial processes like steam‐reforming of methane. [ 12 ] As the storage of H 2 is trickier, ammonia (NH 3 ) has been recognized as a potential option for H 2 storage due to its high hydrogen content and is the backbone of fertilizer industries. Currently, NH 3 is prepared by the Bosch–Haber process, which is not very economical and consumes a huge amount of energy due to its harsh reaction requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, single-atom Pt modified triazine framework (CTF) nanosheets (Pt-SACs/CTF) was developed for the photocatalytic NH3 production. 108 It was found that the Pt-N3 sites were formed in Pt-SACs/CTF, leading to more negative conduction band position with accelerated thermodynamics and fast interfacial charge migration ability, and therefore a high NH3 production rate of 171.4 µmol g -1 h -1 under visible light irradiation. Most recently, we synthesized a ternary Ru/RuO2/g-C3N4 system for N2 photoreduction, which exhibited the photocatalytic NH3 yield of 13.3 µmol g -1 h -1 whilst no NH3 could be measured for pure g-C3N4 under the same condition.…”
Section: Interfacial Modulation Cocatalysts Loadingmentioning
confidence: 99%
“…are utilized as supports to anchor single metal atom. [16][17][18][19] Among them, 2D nanomaterials are regarded as superexcellent supports due to the ultrabroad specific surface area, and unrivaled geometric and electronic structures. [20][21][22] As a recently discovered 2D layered nanomaterials, MXenes with analogous graphene structure represent the transition metal carbides, nitrides, and carbonitride.…”
Section: Introductionmentioning
confidence: 99%